The labor market in Japan, 2000-2018 - Daiji Kawaguchi; Hiroaki Mori (IZA World of Labor, 2019)
As the third-largest economy in the world and a precursor of global trends in population aging, Japan's recent experiences provide important lessons regarding how demographic shifts affect the labor market and individuals' economic well-being. On the whole, the labor market showed a remarkable stability during the financial crisis, despite decades of economic stagnation and sluggish real wage growth. Rapid population aging, however, has brought substantial changes to individuals in the labor market, most notably women, by augmenting labor demand in the healthcare services industry.
Keywords: I11; 330; population aging; gender inequality; healthcare; Japan